Cell and tissue mechanics in cell migration - Lange, Janina; Fabry, Ben (Experimental Cell Research, 2013)

Estimating the 3D pore size distribution of biopolymer networks from directionally biased data. - Lang, Nadine; Münster, Stefan; Metzner, Claus; Krauß, Patrick; Schürmann, Sebastian; Lange, Janina; Aifantis, Katerina E.; Friedrich, Oliver; Fabry, Ben (Biophysical Journal, 2013)
The pore size of biopolymer networks governs their mechanical properties and strongly impacts the behavior of embedded cells. Confocal reflection microscopy and second harmonic generation microscopy are widely used to image biopolymer networks; however, both techniques fail to resolve vertically oriented fibers. Here, we describe how such directionally biased data can be used to estimate the network pore size. We first determine the distribution of distances from random points in the fluid phase to the nearest fiber. This distribution follows a Rayleigh distribution, regardless of isotropy and data bias, and is fully described by a single parameter–the characteristic pore size of the network. The bias of the pore size estimate due to the missing fibers can be corrected by multiplication with the square root of the visible network fraction. We experimentally verify the validity of this approach by comparing our estimates with data obtained using confocal fluorescence microscopy, which represents the full structure of the network. As an important application, we investigate the pore size dependence of collagen and fibrin networks on protein concentration. We find that the pore size decreases with the square root of the concentration, consistent with a total fiber length that scales linearly with concentration.

Microconstriction Arrays for High-Throughput Quantitative Measurements of Cell Mechanical Properties - Lange, Janina; Steinwachs, Julian; Kolb, Thorsten; Lautscham, Lena; Harder, Irina; Whyte, Graeme; Fabry, Ben (Biophysical Journal, 2015)

Migration in Confined 3D Environments Is Determined by a Combination of Adhesiveness, Nuclear Volume, Contractility, and Cell Stiffness - Lautscham, Lena; Kaemmerer, Christoph; Lange, Janina; Kolb, Thorsten; Mark, Christoph; Schilling, Achim; Strissel, Pamela; Strick, Reiner; Gluth, Caroline Laura Maria; Rowat, Amy C.; Metzner, Claus; Fabry, Ben (Biophysical Journal, 2015)
In cancer metastasis and other physiological processes, cells migrate through the three-dimensional (3D) extracellular matrix of connective tissue and must overcome the steric hindrance posed by pores that are smaller than the cells. It is currently assumed that low cell stiffness promotes cell migration through confined spaces, but other factors such as adhesion and traction forces may be equally important. To study 3D migration under confinement in a stiff (1.77 MPa) environment, we use soft lithography to fabricate polydimethylsiloxane (PDMS) devices consisting of linear channel segments with 20 ?m length, 3.7 ?m height, and a decreasing width from 11.2 to 1.7 ?m. To study 3D migration in a soft (550 Pa) environment, we use self-assembled collagen networks with an average pore size of 3 ?m. We then measure the ability of four different cancer cell lines to migrate through these 3D matrices, and correlate the results with cell physical properties including contractility, adhesiveness, cell stiffness, and nuclear volume. Furthermore, we alter cell adhesion by coating the channel walls with different amounts of adhesion proteins, and we increase cell stiffness by overexpression of the nuclear envelope protein lamin A. Although all cell lines are able to migrate through the smallest 1.7 ?m channels, we find significant differences in the migration velocity. Cell migration is impeded in cell lines with larger nuclei, lower adhesiveness, and to a lesser degree also in cells with lower contractility and higher stiffness. Our data show that the ability to overcome the steric hindrance of the matrix cannot be attributed to a single cell property but instead arises from a combination of adhesiveness, nuclear volume, contractility, and cell stiffness.
EVALuna2:17547

Mutated lamin A modulates stiffness in muscle cells - Chatzifrangkeskou, Maria; Kah, Delf-Thorge Eric; Lange, Janina; Goldmann, Wolfgang; Muchir, Antoine (Biochemical and Biophysical Research Communications, 2020)
The cytoskeleton is a complex network interlinking filaments that extend throughout the cytoplasm from the nucleus to the plasma membrane. Three major types of filaments are found in the cytoskeleton: actin filaments, microtubules, and intermediate filaments. They play a key role in the ability of cells to both resist mechanical stress and generate force. However, the precise involvement of intermediate filament proteins in these processes remains unclear. Here, we focused on nuclear A-type lamins, which are connected to the cytoskeleton via the Linker of Nucleoskeleton and Cytoskeleton (LINC) complex. Using micro-constriction rheology, we investigated the impact of A-type lamins (p.H222P) mutation on the mechanical properties of muscle cells. We demonstrate that the expression of point mutation of lamin A in muscle cells increases cellular stiffness compared with cells expressing wild type lamin A and that the chemical agent selumetinib, an inhibitor of the ERK1/2 signaling, reversed the mechanical alterations in mutated cells. These results highlight the interplay between A-type lamins and mechano-signaling, which are supported by cell biology measurements.
CRIS-Team Scopus Importer:2020-06-19
Keywords: A-type lamin (LMNA); Cell mechanical properties; Cell nucleus; Chemical substance selumetinib; ERK1/2 signaling; Micro-constriction rheology

Parameter-free binarization and skeletonization of fiber networks from confocal image stacks - Krauß, Patrick; Metzner, Claus; Lange, Janina; Lang, Nadine; Fabry, Ben (PLoS ONE, 2012)
We present a method to reconstruct a disordered network of thin biopolymers, such as collagen gels, from three-dimensional (3D) image stacks recorded with a confocal microscope. The method is based on a template matching algorithm that simultaneously performs a binarization and skeletonization of the network. The size and intensity pattern of the template is automatically adapted to the input data so that the method is scale invariant and generic. Furthermore, the template matching threshold is iteratively optimized to ensure that the final skeletonized network obeys a universal property of voxelized random line networks, namely, solid-phase voxels have most likely three solid-phase neighbors in a 3×3×3 neighborhood. This optimization criterion makes our method free of user-defined parameters and the output exceptionally robust against imaging noise. © 2012 Krauss et a

Pressure-driven collective growth mechanism of planar cell colonies. - Metzner, Claus; Lange, Janina; Krauß, Patrick; Wunderling, Nico; Übelacker, Julian; Martin, Florian; Fabry, Ben (Journal of Physics D-Applied Physics, 2018)

Unbiased High-Precision Cell Mechanical Measurements with Microconstrictions - Lange, Janina; Metzner, Claus; Richter, Sebastian; Schneider, Werner; Spermann, Monika; Kolb, Thorsten; Whyte, Graeme; Fabry, Ben (Biophysical Journal, 2017)

αvβ3 integrin expression increases elasticity in human melanoma cells - Lacaria, Leda; Lange, Janina; Goldmann, Wolfgang; Rico, Felix; Alonso, José Luis (Biochemical and Biophysical Research Communications, 2020)
Living cells interact with the extracellular matrix (ECM) transducing biochemical signals into mechanical cues and vice versa. Thanks to this mechano-transduction process, cells modify their internal organization and upregulate their physiological functions differently. In this complex mechanism integrins play a fundamental role, connecting the extracellular matrix with the cytoskeleton. Cytoskeletal rearrangements, such as the increase of the overall contractility, impact cell mechanical properties, the entire cell stiffness, and cell deformability. How cell mechanics is influenced via different integrins and their interaction with ECM in health and disease is still unclear. Here, we investigated the influence of αvβ3 integrin expression on the mechanics of human melanoma M21 cells using atomic force microscopy and micro-constriction. Evidence is provided that (i) αvβ3 integrin expression in human melanoma cells increases cell stiffness in both adherent and non-adherent conditions; (ii) replacing αvβ3 with αIIbβ3 integrin in melanoma cells, cell stiffness is increased under adherent, while decreased under non-adherent conditions; (iii) αvβ3 integrin cell stiffening is also maintained when cells adhere to fibronectin, but this phenomenon does not strongly depend on the fibronectin concentration. In all, this study sheds light on the role of αvβ3 in regulating cellular mechanics.
CRIS-Team Scopus Importer:2020-03-20
Keywords: and αIIbβ3; Atomic force microscopy; Cell elasticity; Integrin αvβ3; M21 human melanoma cell; Micro-constrictions; α5β1